2019
DOI: 10.1371/journal.pntd.0007799
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium abscessus infection in the stomach of patients with various gastric symptoms

Abstract: Development of gastric diseases such as gastritis, peptic ulcer and gastric cancer is often associated with several biotic and abiotic factors. Helicobacter pylori infection is such a well-known biotic factor. However, not all H. pylori-infected individuals develop gastric diseases and not all individuals with gastric diseases are infected with H. pylori. Therefore, it is possible that other gastric bacteria may contribute to the formation and progression of gastric disease. The aim of this study was to isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…The results of Caruso et al [ 10 ] showed that the hospital infection rate after laparoscopic surgery for gastric cancer was higher, which may be related to the fact that the study reported total hospital infections and not just lung infections. In addition, Chouhan et al reported [ 11 ] that the incidence of pulmonary infection in elderly patients after laparoscopic radical gastrectomy was about 3%, significantly lower than that in this study, which may be caused by the small sample size of this study. Blood glucose levels are generally high in patients with diabetes mellitus, microangiopathy is often present, and the phagocytic ability of macrophages decreased in varying degrees, which decreased the immune ability of the body and finally increased the risk of pulmonary infection.…”
Section: Discussioncontrasting
confidence: 74%
“…The results of Caruso et al [ 10 ] showed that the hospital infection rate after laparoscopic surgery for gastric cancer was higher, which may be related to the fact that the study reported total hospital infections and not just lung infections. In addition, Chouhan et al reported [ 11 ] that the incidence of pulmonary infection in elderly patients after laparoscopic radical gastrectomy was about 3%, significantly lower than that in this study, which may be caused by the small sample size of this study. Blood glucose levels are generally high in patients with diabetes mellitus, microangiopathy is often present, and the phagocytic ability of macrophages decreased in varying degrees, which decreased the immune ability of the body and finally increased the risk of pulmonary infection.…”
Section: Discussioncontrasting
confidence: 74%
“…Anatomical or functional abnormalities of the upper aerodigestive tract might be an underappreciated risk factor for MAB pulmonary disease. MAB has been demonstrated in 74% of patients with gastric symptoms in their biopsied gastric epithelium [ 34 ]. More studies are warranted to quantify the risks of such upper aerodigestive tract abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…MAB has been demonstrated in 74% of patients with gastric symptoms in their biopsied gastric epithelium [34]. More studies are warranted to quantify the risks of such upper aerodigestive tract abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…However, individuals with gastric diseases such as gastritis, peptic ulcers, and gastric cancer have colonization of M . abscessus [ 34 ]. Before the development of more effective anti-HIV treatment, the gut appeared to be one of the major portals of M. avium infection in AIDS patients with disseminated NTM disease [ 35 ].…”
Section: Epidemiological and Clinical Aspects Of Non-tuberculosis mentioning
confidence: 99%
“…The majority of healthy humans exposed to NTM through an aerosol or drinking water and through immune control of NTMs do not become infected nor show clinical symptoms through the stomach route [33]. However, individuals with gastric diseases such as gastritis, peptic ulcers, and gastric cancer have colonization of M. abscessus [34]. Before the development of more effective anti-HIV treatment, the gut appeared to be one of the major portals of M. avium infection in AIDS patients with disseminated NTM disease [35].…”
Section: Epidemiological and Clinical Aspects Of Non-tuberculosis Mycobacterial Infection And Diseasementioning
confidence: 99%